The Productivity Impact of Business Mobility: International Evidence - Mariacristina Piva; Massimiliano Tani; Marco Vivarelli (Global Labor Organization (GLO), 2017)
The aim of this paper is to investigate the productivity impact of business visits, relative to traditional drivers of productivity enhancement, namely capital formation and R&D. To carry out the analysis, we combine unique and novel data on business visits sourced from the U.S. National Business Travel Association with OECD data on R&D and capital formation. The resulting unbalanced panel covers on average 16 sectors per year in 10 countries during the period 1998-2011 (2,262 observations). Our results suggest that mobility through business visits is an effective mechanism to improve productivity. The estimated effect is about half as large as investing in R&D, supporting viewing business visits as a form of long-term investment rather than pure consumption expenditure. In a nutshell, our outcomes support the need to recognize the private and social value of business mobility.
Keywords: O33; 330; Business visits; labour mobility; knowledge; R&D; productivity